Strategy for Optimizing the Functioning of the Vacuum Block at the Technolohical Equipments - Melikov, E.A.; Magerramova, T.M. (Herald of Azerbaijan Engineering Academy, 2023)
In the submitted article, on the basis of a comprehensive analysis and study of the peculiarities for the complex processes occurring at the oil primary processing installation, (electro-desalting plant of atmospheric-vacuum tube type) the issues of developing a mathematical statement of the optimization problem for one of the important technological blocks of the investigated technological complex - the vacuum block are considered. The experience of operating a process installation in recent years shows that changes in both the quality and consumption of processed oil over a wide range are random in time. The main reason for this is that oil, as a raw material, supplied for processing to the installation from different wells, has different quality indicators. Therefore, the necessity of using, in this case, the approach and method of stochastic programming to the problem for the optimizing the functioning of the object under study with probabilistic constraints is substantiated.